Defining a cluster market: The case of the Korean internet portal service market - Youngsun Kwon (International Telecommunications Society (ITS), 2014)
In a cluster market, many related and unrelated products or services are sold. Examples of cluster markets are Tesco, Sears, Carrefour, Walmart, JCPenny, and Meijer. Because of certain unique characteristics of cluster markets, studies of cluster market definition have been very scant. This paper reviews the market definition issues of cluster markets, proposes a statistical market definition method for cluster markets, and applies the method to the Korean Internet portal service market. The results of analyses show that there is one market for the Korean Internet portals and confirm the concern that the a priori definition of the Internet portal service market using a representative group of services like 1S4C, which was used by the Korea Fair Trade Commission in 2008, did not reflect the actual structure of competition in the Korean Internet portal service market. According to the analyses, the third ranked player in the Korean Internet portal service market, Nate, is more akin to a specialty service provider, not a player competing in the cluster market with Naver and Daum.
Keywords: 330; Cluster Market; Market Definition; Internet Portal; Click Data; Cluster Analysis; Republic of Korea